The Portrayal of Contemporary Love in NIKI’s Dancing with the Devil Song - Dea Hernawati Yuniar (Institut Seni Indonesia Denpasar, 2024)
Purpose: This research paper looks at how modern love is represented in NIKI’s “Dancing with the Devil” song. The perspective of changing ways of expressing love due to digital media is overlooked in the analysis of the song. It signifies that love no longer follows traditional norms, which makes it liberating albeit more intricate when it comes to relating. method: this study employs semiotic phenomenology approach by Peirce, the paper interprets this piece to reveal its deeper imtentions as well as cultural context, revealing the new understanding of youth on love. Result and discussion: the song narrates about an artist who had complicated experiences related to love and were ironic, desperate, thrilled in having a destructive relationship with oneself but addictive too. Implication: this article’s analysis contextualizes on these themes within a greater society where instant gratification often triumphs over meaningful relationships leading people into endless chasing without any end solution. The dynamic of society consequently creating new norms that is adaptable. However, the gratification of shallow love in dating society needs to be studied even further in the application of real society.